Boyden's triad: the past, present and future. (13th November 2021) - Zhang, Min; Mao, Ning; Wu, Qingchen; Tie, Hongtao; Ge, Mingjian
Abstract: OBJECTIVES: The B 3 downwards-shifting malformation was first proposed by Boyden in 1950. Here, we report 14 cases of this malformation in the right lung and the first case of segmentectomy for this malformation. METHODS: All patients with pulmonary lesions underwent three-dimensional computed tomography bronchography and angiography (3D-CTBA) between January 2019 and January 2020, prior to surgery. A consecutive 2356 patients were included, and 14 cases of this malformation were identified; bronchovascular patterns were analysed in each patient. RESULTS: The incidence of this malformation was 0.6%. It was further divided into 3 types: over downwards-shift, partial downwards-shift and normal downwards-shift. The normal downwards-shift type was the most common (8/14), where B 3 shifted downwards completely to merge with B 4 + 5 . In the partial downwards-shift (5/14), only part of the B 3 shifted. In the over downwards-shift type (1/14), both B 3 and B 1 b shifted downwards. A bifurcated right upper lobe （RUL) bronchus (B 1 defective) was observed in 3 cases. The incidence of V 1 a, V 1 b, V 2 a, V 2 b, V 2 c, V 3 a, V 3 b and V 3 c was 100% (14/14). The incidence rates of A 1, A 3 a and A 3 b were 100% (14/14). The incidence of A 2 rec and A 2 asc was 92.9% (13/14) and 71.4% (10/14), respectively. CONCLUSIONS: The B 3 downwards-shifting malformation or 'Boyden's triad' is a rare anomaly. Anatomical exploration of this malformation is important for surgery. Abstract : The right middle lobe (RML) has the smallest volume of all lung lobes.